Safety and immune response after two-dose meningococcal C conjugate immunization in HIV-infected children and adolescents in Rio de Janeiro, Brazil. Issue 50 (15th December 2017) - Frota, Ana Cristina C.; Ferreira, Bianca; Harrison, Lee H.; Pereira, Gisele S.; Pereira-Manfro, Wania; Machado, Elizabeth S.; de Oliveira, Ricardo Hugo; Abreu, Thalita F.; Milagres, Lucimar G.; Hofer, Cristina B.
Highlights: Two-dose meningococcal conjugate vaccine in HIV-pediatric subjects is immunogenic. High seroprotection rate occurs 12–18 months after priming. A booster dose of meningococcal conjugate vaccine is safe. Undetectable viral load and higher CD4 percent were associated with seroprotection. Abstract: We aimed to evaluate immunogenicity and adverse events (AEs) after a booster dose of Meningococcal C conjugated (MCC) vaccine in HIV-infected children and adolescents, who had a previous low seroconversion rate after priming with MCC, at a reference HIV-care center in Rio de Janeiro. Methods: 2–18 years old HIV-infected subjects with CD4+ T-lymphocyte cell (CD4) ≥15%, without active infection or antibiotic use, were enrolled to receive 2 doses of conjugated meningococcal C oligosaccharide-CRM197 12–18 months apart. All patients were evaluated before and 1–2 months after immunization for seroprotection [defined as human serum bactericidal activity (hSBA) titer ≥1:4]. AEs were assessed at 20 min, 3 and 7 days after each dose. Factors independently associated with seroprotection were studied. Results: 156 subjects were enrolled and 137 received a booster MCC dose. 55% were female, and median age was 12 years. Eight-nine percent were receiving combined antiretroviral therapy (cART) at the booster visit (median duration of 7.7 years), 59.9% had undetectable viral load (VL) at baseline, and 56.2% at the booster visit. Seroprotection was achieved in 78.8% (108/137) subjects, with a significantly higher GMT than after the priming dose (p < 0.01). Mild AEs were experienced after a second MCC dose (38%). In logistic regression, undetectable viral load at entry [odds ratio (OR) = 7.1, 95% confidence interval (95%CI): 2.14–23.37], and probably higher CD4 percent at the booster immunization visit (OR): 1.1, 95%CI: 1.01–1.17 were associated with seroprotection after a booster dose of MCC. Conclusion: A booster dose of MCC was safe and induced high seroprotection rate even 12–18 months after priming. MCC should be administered after maximum virologic suppression has been achieved. These results support the recommendation of 2-dose of MCC for primary immunization in HIV-infected children and adolescents with restored immune function.